Coral reef - Sayre, April Pulley (New York : Twenty-First Century, 1996)
Describes the physical features of a coral reef, its community of plants and animals, and environmental threats.
Includes bibliographical references and index.
Keywords: Coral reefs and islands; Coral reef ecology; Ecology